Capturing, Analysing and Interpreting the Complexities of Built Heritage in Historic Cities: Cultural Approaches and BIM Methodologies for Appropriate Conservation - Alayudin, Ammar Zuhdi Bin Mohd; González-Longo, Cristina (MAJ - Malaysia Architectural Journal, 2025)
Built heritage is a key contributor to the quality of the environment in historic cities and its conservation requires a cultural approach and specific tools and methodologies to analyse and interpret its complexities. In an increasingly globalized world, it is important to conserve the character, materiality and richness of built heritage, while allowing adaptations to address current and future energy and climate issues. One of the main challenges is the perceived need for extensive retrofitting of buildings, without providing specific evidence from surveys, testing, monitoring and overall building analysis and assessments. Although Building Information Modelling (BIM) was created for designing new buildings, it is often presented as a solution to intervene in existing ones. By reviewing the relevant literature and using a case study, this paper discusses the current approaches, methods and tools concerning the use of BIM for architectural conservation and retrofitting purposes, focusing on accuracy, interoperability and integration issues. It discusses the current methodologies and the technical shortcomings in creating an accurate and reliable digital representation of existing buildings, vital to assess their condition and design the intervention, beyond the simple documentation. The findings indicate that, although BIM software is quite developed, current methodologies extensively rely on manual and labour-intensive processes, error-prone and contradicting the BIM principle of efficiency. There is also clear lack of integration of BIM and Building Performance Simulation (BPS), and thereafter a lack of comprehensive project collaboration and understanding of the building’s performance. Overall, the focus is currently on the individual tools rather than on the wider cultural approach and more scientific assessments of BIM efficiency and accuracy when used in existing buildings are needed.